Geskiedskrywing - Oliver, E. (Hervormde teologiese studies, 1993)
Writing history History itself can be experienced as a frightening subject for students. The intention of this article is to help students who come face to face with the reality of studying history from a theological point of view to understand and know some of the basics of history and the methods of writing history.